Identification of tgh-2, a Filarial Nematode Homolog of Caenorhabditis elegans daf-7 and Human Transforming Growth Factor β, Expressed in Microfilarial and Adult Stages of Brugia malayi - Gomez-Escobar, Natalia (American Society for Microbiology, 2000)
A novel member of the transforming growth factor β (TGF-β) family has been identified in the filarial nematode parasite Brugia malayi by searching the recently developed Expressed Sequence Tag (EST) database produced by the Filarial Genome Project. Designated tgh-2, this new gene shows most similarity to a key product regulating dauer larva formation in Caenorhabditis elegans (DAF-7) and to the human down-modulatory cytokine TGF-β. Homology to DAF-7 extends throughout the length of the 349-amino-acid (aa) protein, which is divided into an N-terminal 237 aa, including a putative signal sequence, a 4-aa basic cleavage site, and a 108-aa C-terminal active domain. Similarity to human TGF-β is restricted to the C-terminal domain, over which there is a 32% identity between TGH-2 and TGF-β1, including every cysteine residue. Expression of tgh-2 mRNA has been measured over the filarial life cycle. It is maximal in the microfilarial stage, with lower levels of activity around the time of molting within the mammal, but continues to be expressed by mature adult male and female parasites. Expression in both the microfilaria, which is in a state of arrested development, and the adult, which is terminally differentiated, indicates that tgh-2 may play a role other than purely developmental. This is consistent with our observation that TGH-2 is secreted by adult worms in vitro. Recombinant TGH-2 expressed in baculovirus shows a low level of binding to TGF-β-receptor bearing mink lung epithelial cells (MELCs), which is partially inhibited (16 to 39%) with human TGF-β, and activates plasminogen activator inhibitor-1 transcription in MELCs, a marker for TGF-β-mediated transduction. Further tests will be required to establish whether the major role of B. malayi TGH-2 (Bm-TGH-2) is to modulate the host immune response via the TGF-β pathway.